Analisis Implementasi Insentif Pajak Terkait Covid-19 Pada Rumah Sakit - Deden Tarmidi; Rhona Hafidz Dzafron Achmad (Universitas 17 Agustus 1945 Jakarta, 2022)
This study aims to determine the impact of the implementation of tax incentives related to Covid-19 on Hospital X's financial report. The research method used is descriptive qualitative on financial statements and tax reports, especially tax incentives utilized by Hospital X, namely Income Tax Incentive 21 and Income Tax Incentive 25. The results of the analysis in this study found that the utilization of tax incentives at Hospital X has an impact on the company's commercial statements both on company profits, cash flow and balance sheets, while only Income Tax Incentive 25 has an impact on fiscal reports. These results contribute in the form of information to taxpayers in general who have the right to utilize tax incentives to use these incentives for the sustainability of the company by carrying out procedures for the rights and obligations to use tax incentives in accordance with applicable regulations. The results of this research also provide a policy contribution for the Government regarding the benefits of tax incentives for taxpayers, so that it can be a consideration for future tax regulations.